Foundations of soft case-based reasoning - Pal, Sankar K; Shiu, Simon C. K (Wiley series on intelligent systems, 2004)
*Provides a self-contained description of this important aspect of information processing and decision support technology. *Presents basic definitions, principles, applications, and a detailed bibliography. *Covers a range of real-world examples including control, data mining, and pattern recognition.